Review of Phosphate Removal From Water by Various Sorbents - Shoma Hore (Web of Journals Publishing, 2023)
Phosphate is a major pollutant that deteriorates water quality. Adsorption technology is amongst the different technologies used to decrease the phosphate levels in water, and has been found to be highly effective even at low phosphate concentrations. La modified bio-ceramisite (La@BC) is a recyclable granular adsorbent. A layered zinc hydroxide (LZH) was synthesized by a simple precipitation method and Industrial by-products (bottom ash (BA)) has gained increasing attentions because of their intriguing characteristic for phosphate removal. Considering the importance of the topic, this study reviews the reported literature in the field of adsorptive removal of phosphate over various adsorbents such as Lanthanum (La)-based adsorbents, bottom ash And Layered zinc hydroxide. Moreover, insights into the adsorption behavior, experimental parameters, mechanisms, and the possible desorption processes of phosphate onto Lanthanum (La)-based adsorbents, bottom ash and Layered zinc hydroxide are also considered. Finally, research challenges and gaps have been highlighted. Based on this review, future research about phosphate removal is also discussed & reviewed.